Awareness of the Electronics Technology Students in Managing their E-waste: An Input for Developing an E-waste Management Policy - Goyal, John Kenneth C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study seeks to gauge the degree of awareness of the VALPOLY Electronics Technology students on E-waste management. A total of 188 VALPOLY EST students enrolled in the academic year 2022-2023 were purposively selected to participate in the research. An adapted and modified survey questionnaire was used to assess VALPOLY EST students' level of awareness and the challenges they faced in managing their e-waste. Frequency counts, percentages, means, the Mann-Whitney U test, and the Kruskal Wallis test were used for statistical analysis and data handling. All questions were rated on a 4-point Likert scale with a 0.5 level of significance. Based on the findings, "Electronic Components" is the most common e-waste generated by the 188 VALPOLY EST students, while "CCTV", "Oven, Heaters, Cookware, Blender", "Washing Machines", and "Printers" are the least common e-waste generated during their technical training in their technical subjects. The majority of students also preferred "Resell to junkshops as scraps" as an e-waste disposal strategy, while "Take to the collection Centre" was the least preferred. The EST students' level of awareness in managing e-wastes was assessed with a grand mean of 2.62, showing that the VALPOLY EST students are "Aware" of managing their e-wastes. There is no significant difference in the degree of understanding of VALPOLY EST students on e-waste management based on age or gender, but there is a significant difference based on year level. The assessment of the VALPOLY EST students' concerns in managing their e-waste received a grand mean of 3.42, suggesting that the VALPOLY EST students "Strongly Agree" that there are challenges in managing their e-waste. Input through a set of recommendations was made to strengthen the institution's policy on controlling and treating waste and electronic waste.